A two‐step strategy for quality control of Xin‐Yu‐Tie‐Pian, an ointment patch. (25th August 2021) - Chen, Xuezhao; Zhang, Xiaoyong; Li, Wei; Li, Shouxin; Ma, Shenglin; Tian, Jingkui
Abstract: Xin‐Yu‐Tie‐Pian, an ointment patch which is composed of Tetradium ruticarpum and Asarum sieboldii Miquel, can be used for curing recurrent oral ulcers owing to its good bioactivities. Currently, the lack of a method for its quality evaluation hinders the development and clinical application of Xin‐Yu‐Tie‐Pian. Thus, it is necessary to perform research on quality control. The chromatographic fingerprint, as an identification method, and the simultaneous determination method for two bioactive constituents, evodiamine and rutecarpine, can be used to evaluate the quality of traditional medicine. In this study, a two‐step strategy including fingerprint analysis for identification and a simultaneous determination method for two bioactive constituents was performed for Xin‐Yu‐Tie‐Pian quality control. The fingerprint analysis was validated by stability, precision and repeatability tests and a similarity evaluation was performed with 10 selected characteristic fingerprint peaks of 10 batches of Xin‐Yu‐Tie‐Pian patch. Meanwhile, the simultaneous determination method was evaluated by methodological experiments, including linearity, accuracy, repeatability, stability and feasibility. Finally, the results indicate that this two‐step strategy, including HPLC fingerprint analysis and simultaneous determination method, can be successfully applied for the assessment of the quality and quantity of Xin‐Yu‐Tie‐Pian.